Risk aversion, managerial reputation, and debt-equity conflict - Anna Dodonova (Games, 2022)
When a firm finances a new project by issuing debt, it has an incentive to invest in excessively high-risk projects because shareholders enjoy all the benefits in case the project is successful but have limited liability when it fails. Anticipating such behavior, creditors may require a higher interest rate or may even refuse to provide capital. This debt-equity conflict is alleviated by the fact that most investment decisions are made by risk-averse managers who are not as well diversified as shareholders. This paper investigates the debt-equity conflict in firms in which the managers have an unobservable degree of risk averseness. Since managerial risk averseness is a desirable quality, such asymmetric information makes managers undertake actions that increase the market's perception of them as being highly risk-averse. Consequently, such reputation building leads to a lower number of excessively high-risk projects being undertaken. This paper compares the entrepreneurial economy, in which managers are the sole owners of the firms, with the corporate economy, in which managers are hired by shareholders. Using the overlapping generations model, this paper shows that managerial reputation building can partially resolve the debt-equity conflict and improve efficiency in both economies; however, such improvement is larger in the entrepreneurial economy.
Keywords: 330; debt-equity conflict; managerial reputation; risk attitude